Optimization of Prevention of Hazards MV. Meratus Kariangau Ship Running Across Entering the Narrow Waterflow of the Barito River - Ramadhannur, Muhammad Rivaldi; Mudiyanto, Mudiyanto; Wiyono, Teguh (Universitas Hang Tuah, 2024)
This research aims to Optimize the Prevention of the Occurrence of Shipwreck Hazard of MV Meratus Kariangau when Entering the Narrow Shipping Channel of the Barito River. This research method uses a qualitative method with a descriptive approach. For primary data collection techniques obtained from the results of interviews and observations, while for secondary data collection techniques obtained from tidal data in the Barito river, then from journals related to this research, books and others. The results of this study indicate are a). Indication of overdraft when entering the narrow shipping channel, b). Lack of attention to UKC and Tidal Tables, c). Human error from the watch officer who did not pay attention to the tide list. Preparations that must be made by the MV. Meratus Kariangau before entering the narrow shipping channel of the Barito river to avoid the danger of running aground are a) The duty officer and the skipper must operate the navigation equipment on the ship, for example Radar, Echo sounder, GPS. b) The duty officer prepares a map of the narrow shipping channel to be passed. c) The duty officer asks the Engine Control Room (ECR) to ensure that the engine is ready to pass through the narrow shipping channel d) The duty officer calculates the UKC and Squat on the shipping channel to be passed e) The crew conducts a grounding drill to know their duties and responsibilities when running aground f) The skipper and duty officer apply P2TL rule 9 on Narrow channel.